WHO PUT THE ‘SOCIAL’ IN MOBILE AND SOCIAL PAYMENT PLATFORMS? RE-READING SIMMEL AND COLLEAGUES IN LIGHT OF THE CAMBRIAN EXPLOSION - Riedl, Martin Johannes (AoIR Selected Papers of Internet Research, 2018)
This research considers the Cambrian explosion (Nelms, Maurer, Swartz, & Mainwaring, 2017) of mobile and social payment technologies from a perspective that integrates classical theorizing on money and payments (Mauss, 2002; Simmel, 2005) and more recent work (Bandelj, Wherry, & Zelizer, 2017; Dodd, 2014; Maurer, 2015; Zelizer, 2017), as well as research coming out of the $2 and $2 at the $2 at Amsterdam. The paper negotiates mobile and social payment apps and the social realities that they stand upon and applies theoretical viewpoints from these key authors to the emerging technologies, based on a contemporary investigation of what 'social' entails in social payment spaces. The empirical core of this work-in-progress employs the walkthrough method (Light et al., 2016), and compares select mobile and social payment platforms. Furthermore, researchers content-analyze app store screenshots, as well as app descriptions and user comments. Preliminary analysis maps these apps on a continuum of sociality/publicness, with Venmo and its social feed on the liberal side of the spectrum, apps that integrate into messenger services in the middle (e.g. Apple Pay Cash, Square Cash, Google Pay), and apps borne out of banking (Zelle) on the conservative side. Criteria for analysis follow conceptual categories from the literature, such as visibility, objectivity, freedom from everything personal, gifting, earmarking capacities, and other features.